2002
DOI: 10.2320/matertrans.43.1599
|View full text |Cite
|
Sign up to set email alerts
|

Copper Wires for High Speed Logic LSI Prepared by Low Pressure Long Throw Sputtering Method

Abstract: Copper sputtering method for fabrication of high performance logic LSI was studied. Extension of target to substrate distance is effective to improve step coverage of sputtered film combined with reduced operation pressure.Step coverage of low pressure long throw sputtering method also strongly depends upon the feature size of trenches and holes which are formed on silicon wafer. Sub-micron holes and trenches are successfully filled with copper by using this sputtering process followed by re-flow annealing pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Therefore, abruptly decreasing coating thicknesses at the slope and the bottom of the grooves are expected not only in DCMS mode, but also in HiPIMS mode, since an enhanced ionization of sputtered target material is not apparent as outlined above. The step coverage was also shown to be influenced by the particle mean free path, which in turn is affected by the Ar pressure [41][42][43]. Saito et al [42] varied the process pressure and demonstrated that a particle mean free path resembling the target-to-substrate distance yielded the best step coverage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, abruptly decreasing coating thicknesses at the slope and the bottom of the grooves are expected not only in DCMS mode, but also in HiPIMS mode, since an enhanced ionization of sputtered target material is not apparent as outlined above. The step coverage was also shown to be influenced by the particle mean free path, which in turn is affected by the Ar pressure [41][42][43]. Saito et al [42] varied the process pressure and demonstrated that a particle mean free path resembling the target-to-substrate distance yielded the best step coverage.…”
Section: Resultsmentioning
confidence: 99%
“…The step coverage was also shown to be influenced by the particle mean free path, which in turn is affected by the Ar pressure [41][42][43]. Saito et al [42] varied the process pressure and demonstrated that a particle mean free path resembling the target-to-substrate distance yielded the best step coverage. In our study, Ar pressures between 500 and 800 mPa result in a Figure 2 Growth rates as a function of the process pressure for B 4 C coatings deposited at the substrate temperatures of 100°C (black) and 400°C (red) using DCMS (squares) and HiPIMS (triangles).…”
Section: Resultsmentioning
confidence: 99%
“…To obtain a conformal film in the high aspect ratio via structure, the angular flux of the sputtered Cu toward to the bottom of the deep via needs to be enhanced to produce a relatively thick film at the contact bottom [6]. As the distance between target and substrate increases, the range of the angle of the atomic flux that is reaching the substrate is decreased naturally such that the deposition can be added to the bottom of the structure [7,8].…”
Section: Introductionmentioning
confidence: 99%